2007
DOI: 10.1111/j.1742-6723.2007.00915.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in patients with an emergency department diagnosis of fever of unknown origin

Abstract: Fever of unknown origin is diagnosed less frequently in adults than in children. Adult patients are more likely to be admitted, have longer lengths of stay and have positive blood cultures. Although FUO is diagnosed infrequently in the ED, blood cultures remain useful in the evaluation of unexplained fever, particularly in adults as age increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
7
0
2
Order By: Relevance
“…FUO is diagnosed less frequently in adults than in children; however, adult patients are more likely to be admitted and have longer LOSs. [39] The mean age of patients with unexplained fever in medical centers was 21.53 ± 2.50 years, whereas that of patients with idiopathic fever in regional hospitals was 16.63 ± 2.44 years. The mean Charlson comorbidity indexes in medical centers and regional hospitals were 0.37 ± 0.095 and 0.30 ± 0.093, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…FUO is diagnosed less frequently in adults than in children; however, adult patients are more likely to be admitted and have longer LOSs. [39] The mean age of patients with unexplained fever in medical centers was 21.53 ± 2.50 years, whereas that of patients with idiopathic fever in regional hospitals was 16.63 ± 2.44 years. The mean Charlson comorbidity indexes in medical centers and regional hospitals were 0.37 ± 0.095 and 0.30 ± 0.093, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…There have been very few systematic studies of UFI in the Australian setting, with those that have been performed suggesting that a large proportion of UFI remains undiagnosed. A 3-year retrospective study in Western Australia between July 2000 and July 2003 identified 218 UFI cases, of which two-thirds were children ( Ingarfield et al, 2007 ). Another retrospective study conducted in North Queensland from July 2008 to June 2011 showed 58.8% of patients as having no definitive diagnosis for their undifferentiated fever ( Susilawati and McBride, 2014 ).…”
Section: Ufi Diagnosis In Australiamentioning
confidence: 99%
“…6,16 Kuman terbanyak pada biakan darah pasien dengan demam berkepanjangan adalah Staphylococcus epidermidis yakni 8/13, berbeda dengan penelitian oleh Berezin dkk, 17 Ingarfield dkk, 18 21 Berdasarkan data tersebut, bakteremia pada penelitian ini lebih mendekati bakteremia pada pasien yang tidak mengalami demam berkepanjangan. Hal ini salah satunya dapat menunjukkan bahwa pelayanan kesehatan di negara kita masih belum memadai dibandingkan negara maju karena pemeriksaan biakan masih dinilai mahal sehingga tidak selalu dikerjakan.…”
Section: Pembahasanunclassified